Peran Kelompok Budidaya Ikan Patin Dalam Meningkatkan Ekonomi Keluarga Di Desa Triyoso, Kecamatan Belitang, Kabupaten Oku Timur - Mutiara, Yona Prastika; Nengsih, Yanti Karmila; Husin, Azizah (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
This research was conducted to reveal the role of the Sari Patin Patchouli fish farming group (Pokdakan) in improving the household economy. This research was conducted in Triyoso Village, Belitang District, East OKU Regency. This research is included in the type of descriptive research and uses the Mixed Methods approach which combines data in the form of qualitative data obtained from the results of interviews with 3 group administrators and 2 group members as well as observational data and quantitative data obtained from the results of a questionnaire conducted with a sample of all group members Sari Patin patchouli cultivation, namely 14 people. The results of this study describe that there are several roles in the Sari Patin Nilam fish farming group which influence the increase in the household economy which is reinforced by the results of the questionnaire, including the role as a learning class with a percentage of 100%, as a production unit with a percentage of 96%, as a business units with a percentage of 86% and as a place of cooperation with a percentage of 100%. The existence of this role has an effect on increasing the family economy, this translates into an increase in income of 80%, an increase in purchasing power of 73% and an increase in savings of 80%, from the results of research conducted, it can be concluded that with the presence of several of these roles in the Patchouli cultivation group Sari Patin has proven to be able to improve the family economy for members of the Sari Patin Patchouli cultivation group.